The Association between Door-to-Balloon Time of Less Than 60 Minutes and Prognosis of Patients Developing ST Segment Elevation Myocardial Infarction and Undergoing Primary Percutaneous Coronary Intervention. (4th April 2017) - Chen, Fu-Cheng; Lin, Yan-Ren; Kung, Chia-Te; Cheng, Cheng-I; Li, Chao-Jui
Abstract : Background. The study aimed to verify the effect of primary percutaneous coronary intervention (PPCI) with <60 min door-to-balloon time on ST segment elevation myocardial infarction (STEMI) patients' prognoses. Methods. Outcomes of patients receiving PPCI with door-to-balloon time of <60 min were compared with those of patients receiving PPCI with door-to-balloon time 60–90 min. Result. Totally, 241 STEMI patients (191 with Killip classes I or II) and 104 (71 with Killip classes I or II) received PPCI with door-to-balloon time <60 and 60–90 min, respectively. Killip classes I and II patients with door-to-balloon time <60 min had better thrombolysis in myocardial infarction (TIMI) flow (9.2% fewer patients with TIMI flow <3, p = 0.019 ) and 8.0% lower 30-day mortality rate (p < 0.001 ) than those with 60–90 min. After controlling the confounding factors with logistic regression, patients with door-to-balloon time <60 min had lower incidences of TIMI flow <3 (aOR = 0.4, 95% CI = 0.20–0.76), 30-day recurrent myocardial infarction (aOR = 0.3, 95% CI = 0.10–0.91), and 30-day mortality (aOR = 0.3, 95% CI = 0.09–0.77) than those with 60–90 min. Conclusion. Door-to-balloon time <60 min is associated with better blood flow in the infarct-related artery and lower 30-day recurrent myocardial infarction and 30-day mortality rates.